Crisis-Driven Rebranding and Narrative Strategy: The Transformation of Kutus Kutus into Sanga Sanga - Latifa Ramonita; Deddy Muharman; Chelma Destria; Eka Bella Ferlinda Furkan (Ilomata International Journal of Social Science, 2026)
Rebranding often becomes a strategic imperative, not merely an option, especially when a brand faces massive internal crises and market challenges. This qualitative study examines the rebranding strategy employed by Babe Bambang Pranoto, founder of PT Kutus-Kutus Herbal, in transforming the brand from "Kutus Kutus" to "Sanga Sanga". Through an in-depth analysis of autobiographical narratives, social media content, and public interviews, this research reveals how a defensive-progressive rebranding approach was implemented. The findings indicate that this strategy was constructed and communicated in social media as a means of restoring consumer trust, particularly through authentic storytelling and the strategic use of digital platforms, rather than through empirically measured consumer responses. The brand's repositioning into the premium segment, underpinned by locally resonant cultural symbolism articulated as a branding narrative, and integrate cultural symbolism in support of premium market repositioning. This study provides a valuable conceptual and analytical insights for understanding crisis-driven rebranding, especially for heritage brands navigating legitimacy, authenticity, and identity reconstruction in the digital era. These conclusions are derived from interpretive narrative and communication analysis rather than direct measurement of consumer attitudes or market performance.